Expanding Horizons A Randomized Controlled Trial on Adolescents' Career Information Acquisition - Sofia Badini; Esther Gehrke; Friederike Lenel; Claudia Schupp (CESifo GmbH, 2024)
We implement a randomized controlled trial to investigate whether students in lower-secondary school more effectively acquire information about potential career paths if this information is preceded by a task that allows students to explore their own interests and the career information is presented in personalized order. We find that self-exploration in combination with the personalized display increases students' information acquisition. Students also read about more diverse career paths and shift their focus from occupations that require university education towards those that require a high-school degree.
Keywords: C93; D83; D91; I21; O15; 330; information acquisition; career guidance; education; field experiment